2017
DOI: 10.21037/tau.2017.07.05
|View full text |Cite
|
Sign up to set email alerts
|

Penile prosthesis in the management of erectile dysfunction following cancer therapy

Abstract: Erectile dysfunction (ED) is a common problem in older men and occurs with even greater frequency following the treatment of pelvic malignancies. Inflatable penile prosthesis (IPP) implantation is a safe and effective form of definitive ED treatment for those men who fail more conservative measures, and it can be used with similar outcomes in men following cancer therapy. Although many of these men remain dissatisfied with other therapeutic options for ED, IPPs are underutilized in this population. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Stress urinary incontinence and ED are common patient ailments treated in a urologist's o ce, and its concomitant presentation can be seen in speci c patient populations, such as those who undergo robotic-assisted prostatectomy for prostate cancer [10]. Speci cally, in post-prostatectomy patients, for instance, the PIVOT study showed at 2-year follow-up, 17% of patients had SUI or required indwelling catheter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress urinary incontinence and ED are common patient ailments treated in a urologist's o ce, and its concomitant presentation can be seen in speci c patient populations, such as those who undergo robotic-assisted prostatectomy for prostate cancer [10]. Speci cally, in post-prostatectomy patients, for instance, the PIVOT study showed at 2-year follow-up, 17% of patients had SUI or required indwelling catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, comparisons between these various approaches have previously been conducted assessing risk factors for complications like infection or mechanical failure; with one technique not de nitively determined to be superior over the other [5][6][7][8][9]. However, in certain populations, such as men who have undergone robotic-assisted prostatectomy [10], the presence of both refractory stress urinary incontinence and severe ED may require surgical correction with the use of an IPP and a continence device such as an AUS or urethral sling. The synchronous dual implantation of an IPP and arti cial urinary sphincter (AUS) or bulbourethral sling has previously shown to be effective for concomitant treatment of erectile dysfunction (ED) and SUI [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies about penile rehabilitation followed, mainly focusing on common erectile aids e.g., oral phosphodiesterase type 5 inhibitors (PDE5-I), ICI therapy, intraurethral alprostadil [Medicated Urethral System for Erection (MUSE®)] therapy, and vacuum erection devices (VED) (11,12). For men who fail these more conservative strategies, inflatable penile prosthesis implantation might be a definitive ED treatment (13) with an excellent cost-effectiveness (14). The basic idea of the aforementioned more conservative strategies of penile rehabilitation is prevention of hypoxia in the penile tissue related to cavernous nerve neuropraxia after RP which leads to fibrosis and atrophy of the corporal smooth muscle cells (15).…”
Section: Original Articlementioning
confidence: 99%
“…Penile rehabilitation programs are also increasingly used, although there is no standard rehabilitation protocol and a lack of evidence of efficacy [10]. Penile implants can provide effective early sexual rehabilitation and improve quality of life without compromising surgical outcomes, although utilisation is low [11].…”
Section: Introductionmentioning
confidence: 99%